Meningkatkan Kemampuan Motorik Halus melalui Kegiatan Mozaik pada Anak Usia 5-6 Tahun di TK Markus Medan Helvetia - Panni Ance Lumbantobing; Sondang Purba; Rosnilam Amazihono (Departement of Mathematics Education, 2023)
The purpose of this study was to improve Children fine motor skills through mosaic activities at TK Markus Medan Helvetia. The subjects of this study were children in group B-Three aged 5-6 years totaling 13 children. This research is Classroom Action Research with a descriptive and quantitative approach which was carried out in the second semester in Academic Years of 2021/2022. The data collection technique used in this research is observation with direct observation and documentation. The results of this study indicate that there is an increase of Children fine motor skills through mosaic activities where before the activities the average pre-cycle percentage is 34,62% while after the action there is an increase in the first cycle of 52,56% and increases in the second cycle by 90,38%. So it can be concluded that Mosaic Activities Improve Fine Motor Skills of Children of Group B-Three at TK Markus Medan Helvetia.